Pengaruh Substitusi Sebagian Agregat Halus Dengan Abu Batu Dan Penambahan Fly Ash Terhadap Kuat Tekan Beton - Heronimus Lumenta; Stefanus Tri Bintoro; David Widianto; Widija Suseno (G-SMART, 2019)
The purpose of this research is to determine concrete compressive strengths with screenings variation of 0%, 25%, 50%, and 75% by addition the weight of fine aggregate (sand) and fly ash 15% by the weight of cement. The background of this research is increasing demand for concrete and the limited availability of concrete substances. Therefore innovation is needed to maintain the availability of concrete constituent materials and also to improve the quality of concrete. Up until now a lot of researches have been carried out regarding of substitute materials or added materials that can be substituted in making concrete. Based on this background the writer chose one of the added ingredients that can improve the quality (compressive strength) of concrete, namely fly ash. Fly ash produced from the remaining combustion of coal in the Steam Power Plant (PLTU).  While for substitution materials, the writer used the screenings that substituted by sand. In this study the writer used four variations of concrete with a ratio of 0% screenings : 100% sand, 25% screenings  : 75% sand, 50% screenings  : 50% sand, 75% screenings: 25% sand. Every variant was added with fly ash as much as 15% of the weight of cement.The result of this research was indicated that variations 25% screenings, 75% sand plus  fly ash of the weight of cement that having the highest quality of concrete among the other variations were as much as 298,95 kg/cm2 at the age of 7 days; 403,23 kg/cm2 at the age of 28 days; and 456,53 kg/cm2 at the age of 42 days. This was because means of air vents was in concrete filled by granules of screening so that the concrete became denser and made concrete strong press was increased.